2011
DOI: 10.5572/ajae.2011.5.1.041
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Transportation-Related Greenhouse Gas Emissions in the Port of Busan, S. Korea

Abstract: The port of Busan is the fifth busiest container port in the world in terms of total mass of 20-foot equivalent units transported. Yet no attempts have been made to estimate the greenhouse gas (GHG) emissions from the port of Busan by accounting for all port-related activities of the various transportation modes. With these challenges in mind, this study estimates the first activity-based GHG emissions inventory in the port of Busan, which consists of four transportation modes: marine vessels, cargo-handling e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Cheong et al [61] reported that emissions from ship movements in the Port of Busan (POB) accounted for 32% of all GHG transportation emissions in Busan. Shin and Cheong [62] calculated the GHG emission inventory using a fuel-based approach and data from POB. Chang et al [50] applied the bottom-up approach using data related to fuel consumption and activity time to estimate emissions based on the characteristics and activities of individual ships in the Port of Incheon (POI).…”
Section: Research Demandmentioning
confidence: 99%
“…Cheong et al [61] reported that emissions from ship movements in the Port of Busan (POB) accounted for 32% of all GHG transportation emissions in Busan. Shin and Cheong [62] calculated the GHG emission inventory using a fuel-based approach and data from POB. Chang et al [50] applied the bottom-up approach using data related to fuel consumption and activity time to estimate emissions based on the characteristics and activities of individual ships in the Port of Incheon (POI).…”
Section: Research Demandmentioning
confidence: 99%
“…where FC represents fuel consumption; N represents annual total ship call; DF is average daily fuel consumption by ship type (ton/day); D represents average travel distance in port (km); FE represents average fuel economy by ship tonnage (km/kL); 0.79 is the average hotel time of a ship call per day; and 0.2 means the fuel consumption of hotelling at anchorage and berth will be assumed as 20% of the fuel consumption of full operation. At the regional level, Shin and Cheong [39] generated the GHGs ship emissions at Port of Busan (POB) with a topdown approach. Chang et al [44] firstly used the bottom-up approach to assess the GHGs emissions from ship operations at the Port of Incheon (POI) from January to October 2012 based on the FC method.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They stated that their environmental costs are over $123 million per year. Shin and Cheong 29 calculated GHG emission inventories for the Busan port of South Korea based on activities of marine vessels, cargo handling equipment, heavy-duty diesel vehicles (HDDV), and railroad. They calculated that 36% of the total GHG emissions were caused by CHE and heavy-duty trucks.…”
Section: Literaturementioning
confidence: 99%